Nutrition intervention through stunting education on pregnant and breastfeeding women group - Mukty, Ma'rifat Istiqa; Kusuma, Nina Isywara; Ilyas, Asmiana Saputri; Sulistyaningtyas, Nunik; Daud, Anna Maria; HB, Erlina; Muhammad, Karlyna Bte (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Stunting is one of the public health problems that is still a concern in Indonesia with a high prevalence at both national and local levels. Based on Riskesdas 2020, the prevalence of stunting in Indonesia reached 27.67%, while the national target is 14% by 2024. To support these efforts, Tri Tunas Nasional Institute of Technology and Health in collaboration with Rumah Zakat organized a community service program entitled